Substance, object and models of financial private legal relationship - Pratasavitski, Sergey P. (Journal of the Belarusian State University. Law, 2019)
Substance and object of financial private legal relationship is explored in the paper. It is noted that the existence of financial private legal relationships is brought to the existence of private-law attributes of their parties. In other words, these attributes exist in the form of legal relationship, forming the substance of the latter. Since the private-law attributes of the subjects of the financial private legal relationship constitute its substance, financial property (specific) is the object of this legal relationship. There is no financial private legal relationship without an object. Depending on a structural type of relationship and a kind of financial property, models of financial private legal relationship are stood out, one of which is a financial obligation. It is subjected to a separate analysis. A financial obligation is a legal relationship where one party (the debtor) is obliged to provide money, credit instruments or shares for the benefit of the other party (creditor), and the creditor is entitled to receive them.